1999
DOI: 10.1002/(sici)1099-0682(199906)1999:6<981::aid-ejic981>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Mechanics Force Field for Alkylcobaloximes, a Model of Vitamin B12 Coenzyme – Implications of Steric and Electronic Factors in the Co–C Bond Cleavage

Abstract: Molecular mechanics force field constants have been derived for alkylcobaloximes, (alkyl)Co(DH)2L (DH = monoanion of dimethylglyoxime and L = planar N‐donor ligand), implementing the AMBER force field. Atomic charges have been calculated by the semiempirical ZINDO/1 method. Stretching and bending constants have been calculated by the Badger and Halgren equations, with the introduction of simple functions for the description of the electronic influence of the axial ligands on the coordination geometry. 26 param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…These structural features are in agreement with recent molecular mechanics calculations for LCo(DH) 2 Me (L is a planar N donor ligand) based on a new approach which also takes the contribution of the electronic trans influence into account. [5] These calculations have furnished profiles of the strain energy against the ϕ angle, which is characterised by a large maximum centred at ϕ ϭ 90°and a minimum at ϕ ϭ 0°, the difference in height ranging from 8 to 40 kJ/mol and increasing with the L bulk. [5] In addition, the large maximum at approximately ϕ ϭ 90°has a fine structure, consisting of two nearly equal maxima at about 55°and 145°, separated by a relative minimum at ϕ ϭ 90°.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These structural features are in agreement with recent molecular mechanics calculations for LCo(DH) 2 Me (L is a planar N donor ligand) based on a new approach which also takes the contribution of the electronic trans influence into account. [5] These calculations have furnished profiles of the strain energy against the ϕ angle, which is characterised by a large maximum centred at ϕ ϭ 90°and a minimum at ϕ ϭ 0°, the difference in height ranging from 8 to 40 kJ/mol and increasing with the L bulk. [5] In addition, the large maximum at approximately ϕ ϭ 90°has a fine structure, consisting of two nearly equal maxima at about 55°and 145°, separated by a relative minimum at ϕ ϭ 90°.…”
Section: Discussionmentioning
confidence: 99%
“…[5] These calculations have furnished profiles of the strain energy against the ϕ angle, which is characterised by a large maximum centred at ϕ ϭ 90°and a minimum at ϕ ϭ 0°, the difference in height ranging from 8 to 40 kJ/mol and increasing with the L bulk. [5] In addition, the large maximum at approximately ϕ ϭ 90°has a fine structure, consisting of two nearly equal maxima at about 55°and 145°, separated by a relative minimum at ϕ ϭ 90°. This suggested that orientation C (Scheme 2) is energetically even less favoured than orientation B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed bond lengths in the octahedron of complex 2 can be slightly modified by the packing effects, which can force the molecule into a strained conformation. 29 At the same time, the axial DMF ligand was expected to have lower σ-donor ability in the structure of complex 2. So the bond lengths around the central Ni atom of complex 2 are all slightly shorter than the corresponding ones of compound 1.…”
Section: Crystal Structurementioning
confidence: 99%
“…These studies were useful in understanding the mechanism of Co-C bond cleavage in the vitamin B 12 coenzyme. Marques et al 11 and Randaccio et al 12 studied the molecular mechanism of modelling of cobaloximes. Halpern et al 13 studied the hydrolytic dealkylation of organo-cobaloximes related to coenzyme B 12 .…”
Section: Introductionmentioning
confidence: 99%